Health risk assessment of levels of some toxic metals and polycyclic aromatic hydrocarbons of some commercial soft drinks commonly consumed among students of Nnamdi Azikiwe university, Awka, Anambra state, Nigeria - Ngozi Asomugha, Rose; Emmanuel Igwe, Chijoke; Ukamaka Nome, Peace; Mary Uchendu, Onyinye; Godson, Nwamkwere (International Journal of Pharmacology and Toxicology, 2020)
Food Safety is of growing concern globally, and more so considering the relatively high proportion of soft drinks in the beverage market worldwide, and its rate of consumption especially amongst the youths. It is essential to evaluate the levels of toxic metals and Polycyclic Aromatic Hydrocarbons (PAHs) residues of which when present in soft drinks above the permissible limits could pose serious public health risk. The aim of this present study was to assess the levels of heavy metals (Pb, Hg, Cd ,As) and Polycyclic aromatic Hydrocarbons(PAHs) in 16 commercial soft drinks marketed in Awka, using Atomic Absorption Spectroscopy(AAS) and Flame Ionization detector (GC-FID), respectively. The carcinogenic and non-carcinogenic risk assessment were performed using the method established by United State Environmental Protection agency(USEPA).The data obtained were compared with the permissible limit set for drinking water by United State Environmental Protection Agency(USEPA),World Health Organization (WHO),Standard Organization of Nigeria(SON) and Federal Environmental Protection Agency(FEPA). The highest mean level of 0.6116 mg/l is related to Pb and the lowest of 0.0028mg/l related to Hg. The mean levels of the metals increased in this order: Hg<As<Cd<Pb. For the PAHs, using Benzo(a)pyrene as the benchmark for other PAHs congeners because of its strong carcinogenic potency, is not detected in this study, and thus pose no health risk. The target hazard quotient (THQ) of Hg in the studied samples is less than 1. Pb levels in75% the studied samples had THQ>1, and thus, pose a health risk. The hazard index, calculated as the combined risk of heavy metal toxicity is greater than unity (HI>1).The incremental lifetime cancer risk (ILCR) values estimated for Pb, As and Cd in the sample were 6.25%,31.25% and 25% ,respectively, representing higher than acceptable risk value of (10-6 -10-4) . The results raise a concern for the public exposed with respect to As and Cd carcinogenic risk values.Â Â